KEPEMIMPINAN INKLUSIF GENDER DAN KEBIJAKAN UPAH MINIMUM SEBAGAI STRATEGI MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA EKONOMI DAERAH: ANALISIS PANEL 33 PROVINSI DI INDONESIA 2019–2023 - Hendri Janoari Hartadi; Maria Christiana Iman Kalis; Sulistiowati (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the effects of gender-inclusive leadership—measured by the share of women in managerial positions—and minimum wage policy (UMP) on regional economic performance (real GRDP per capita) in Indonesia. Using panel data for 33 provinces from 2019–2023 compiled from official sources (BPS, ILOSTAT, Ministry of Manpower), we estimate panel regressions with Fixed Effects (FEM) and Random Effects (REM), complemented by the Hausman test, diagnostics (VIF, Breusch–Pagan, White, Durbin–Watson), and descriptive and correlation analyses. The evidence underscores the importance of public HRM strategies that integrate equitable compensation policies with gender-inclusive leadership.